Essential environment : the science behind the stories. - Brennan, Scott, ....-; Withgott, Jay, ....- (San Francisco : Pearson, 2005)
"Environment: The Science Behind the Stories, Brief Version" is an introductory textbook that uses case studies and real data to demonstrate the role of science in solving pressing environmental problems. Dynamic central case studies are integrated throughout each chapter, capturing readers' attention and providing them with a contextual framework on which to build their understanding of concepts in environmental science. Science Behind the Story boxes explain how scientists know what they know about environmental problems, while opposing viewpoints on contentious environmental issues allow readers to hear both sides of the story. With only 14 chapters, the book \f1\b \f0\b0 avoids the encyclopedic approach of other textbooks on the market and instead offers only the essential concepts, theories, and principles of environmental science. In particular, the authors have condensed the material on environmental policy, agriculture, atmosphere, and water, providing the reader with the essential material they need in a more concise, affordable format. An Introduction to Environmental Science, Environmental Economics and Policy, Chemistry, Energy, and Environmental Systems, Ecology and Evolution, Human Population Growth, Soils and Agriculture, Toxicology and Environmental Health, Atmospheric Science, Air Pollution, and Climate Change, Marine and Freshwater Resources, Biodiversity and Conservation Biology, Land Use, Forest Management, and Creating Livable Cities, Nonrenewable Energy Sources and Their Environmental Impacts, Renewable Energy Sources, Waste Management. For all readers interested in using case studies and real data to demonstrate the role of science in solving pressingenvironmental problems.}
Keywords: Milieukunde